Insuring Well-Being? : Buyer's Remorse and Peace of Mind Effects from Insurance - Tafere, Kibrom; Barrett, Christopher B.; Lentz, Erin; Ayana, Birhanu T. (World Bank, Washington, DC, 2017)
This paper estimates the causal effects of index insurance coverage on subjective well-being among livestock herders in southern Ethiopia. The randomization of incentives to purchase index-based livestock insurance and three rounds of panel data are exploited to separately identify ex ante welfare gains from insurance that reduces risk exposure and ex post buyer's remorse effects that may arise after the resolution of uncertainty. Insurance coverage currently in force generates subjective well-being gains that are significantly higher than the buyer's remorse effect of an insurance that lapsed without paying out. Given the temporal correlation in insurance purchase propensity, failure to control for potential buyer's remorse effects can bias downward estimates of welfare gains from current insurance coverage.